2020
DOI: 10.1002/ccr3.2976
|View full text |Cite
|
Sign up to set email alerts
|

Association of olfactory neuropathy spectrum disorder and Wolff‐Parkinson‐White syndrome: A Report of a case

Abstract: Olfactory neuropathy spectrum disorder is characterized by hyposmia or anosmia and hypoplastic or absent olfactory bulbs. There may be an association between olfactory neuropathy spectrum disorder and Wolff‐Parkinson‐White syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It is also not uncommon to find other clinical manifestations, particularly cardiac in these patients. Cases of hypogonadotropic hypogonadism associated with Wolf-Parkinson-White syndrome have been reported in the literature [3,4]. Recent studies have also shown that testosterone deficiency can induce metabolic disorders such as hyperglycemia and the progression of atherosclerotic disease, particularly coronary artery disease [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…It is also not uncommon to find other clinical manifestations, particularly cardiac in these patients. Cases of hypogonadotropic hypogonadism associated with Wolf-Parkinson-White syndrome have been reported in the literature [3,4]. Recent studies have also shown that testosterone deficiency can induce metabolic disorders such as hyperglycemia and the progression of atherosclerotic disease, particularly coronary artery disease [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report [ 1 ] noted an adult patient with previously undiagnosed congenital anosmia as well as the radiographic absence of the olfactory groove/bulbs as well as Wolff-Parkinson-White syndrome. Further investigation revealed a prior case report [ 2 ] involving a patient with isolated hypogonadotropic hypogonadism, pronounced hypodontia, and the Wolff-Parkinson-White syndrome.…”
Section: Introductionmentioning
confidence: 99%